VD_FINDINFO HC / 2010 / 460 vom 23. August 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, APPRÉCIATION DES PREUVES, INTERDICTION DE L'ARBITRAIRE | 17 CPC, 12 LPEBL, 23 al. 1 let. c LPEBL, 7 LPEBL